Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells - Santos, José L. (2019)
A new family of gene delivery vectors is synthesized consisting of a medium-size generation PAMAM dendrimer (generation 5, with amine termini) core randomly linked at the periphery to hydrophobic chains that vary in length (12 to 16 carbon alkyl chains) and number (from 4.2 to 9.7 in average). The idea subjacent to the present work is to join the advantages of the cationic nature of the dendrimer with the capacity of lipids to interact with biological membranes. Unlike other amphiphilic systems designed for the same purpose, where the hydrophobic and hydrophilic moieties coexist in opposite sides, the present vectors have a hydrophilic interior and a hydrophobic corona. The vectors are characterized in respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA are analyzed concerning their size, zeta-potential, resistance to serum nucleases, capacity of being internalized by cells and transfection efficiency. These new vectors show a remarkable capacity for mediating the internalization of pDNA with minimum cytotoxicity, being this effect positively correlated with the -CH(2)- content present in the hydrophobic corona. Gene expression in MSCs, a cell type with relevancy in the regenerative medicine clinical context, is also enhanced using the new vectors but, in this case, the higher efficiency is shown by the vectors containing the smallest hydrophobic chains.